State Policy of Cooperation between Countries and Global Institutions: Condition and Prospects - Vitaliy Shpachuk; Volodymyr Hornyk; Serhiy Kravchenko; Boris Vizirov; Olena Aleinikova; George Abuselidze (E3S Web of Conferences, 2023)
The aim of the work is to analyse the state policy of Ukraine's cooperation with global institutions and, on its basis, to determine the prospects and directions of such cooperation. Methods of grouping, modelling and forecasting, methods of theorizing and historical formalization, as well as methods of system analysis, sampling and description were used to substantiate the prospects and directions of Ukraine's cooperation with global institutions. The study identifies the conceptual principles, areas of relationship and cooperation of Ukraine with international organizations, the problems of relations of domestic state institutions with global organizational structures in modern conditions. The priority goals and measures of the state policy of Ukraine's cooperation with global institutions, the directions of mechanisms of cooperation with international intergovernmental and non-governmental organizations in order to achieve the strategic goals of the state development are outlined.
Keywords: 330